2022
DOI: 10.1155/2022/7785573
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Curative Effects and Influencing Factors of Uterine Artery Chemoembolization Combined with Uterine Curettage Treating with Cesarean Scar Pregnancy Patients

Abstract: Objective. To explore the clinical curative effects of uterine arterial chemoembolization (UACE) combined with uterine curettage treating with cesarean scar pregnancy (CSP) patients, and analyze the influencing factors of postoperative efficacy. Methods. A total of 86 patients with CSP from January 2019 to December 2021 in the Gynecology ward of our hospital were selected and divided into the control group (n = 43) and the observation group (n = 43) according to the random number method. The control group was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Intraoperative angiography allows effective imaging of the anatomy with special attention to the uterine arteries and the possible presence of anastomoses that could hinder the procedure [ 23 ]. The standard dose used in the next step of the procedure is 50 mg of methotrexate, 25 mg in each of the uterine arteries, which directly supply blood to the embryo [ 26 ]. After the MTX is administered, occlusive agents such as polyvinyl alcohol and Gelfoam are injected through a delivery catheter to block the feeding vessel, prevent further blood flow to the gestational foci, and MTX migration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intraoperative angiography allows effective imaging of the anatomy with special attention to the uterine arteries and the possible presence of anastomoses that could hinder the procedure [ 23 ]. The standard dose used in the next step of the procedure is 50 mg of methotrexate, 25 mg in each of the uterine arteries, which directly supply blood to the embryo [ 26 ]. After the MTX is administered, occlusive agents such as polyvinyl alcohol and Gelfoam are injected through a delivery catheter to block the feeding vessel, prevent further blood flow to the gestational foci, and MTX migration.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment efficacy was found to be influenced by size of the gestational mass, presence of fetal heartbeat, and type of CSP. Yu et al evaluated the effectiveness of chemoembolization by comparing it with an injection of methotrexate combined with uterine curettage [ 26 ]. They found that the total effective rate was significantly higher in the group of patients treated with chemoembolization ( P <0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%